Foresight jako instrument wsparcia regulacji prawnych w zakresie odnawialnych źródeł energii - Woźniak, Leszek; Ziółkowski, Bożydar (Foresight as an Instrument for Support of Legal Regulations Within the Scope of Renewable Energy Resources, 2009)
The foresight exercises are used very often to support legal regulations in single countries and regions. In the presented article there are shown some results of foresight research done for Podkarpackie voivodeship in order to develop solutions related to renewable energy. The presented analyses are aimed at pointing out the importance of foresight activities for the support of regional legal regulations referred to renewable energy resources. The conducted analyses are based upon results of Delphi method and sector expert panels which were realized within seven thematic areas.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 83, s. 224-232